JIZZAX VILOYATI IJTIMOIY-IQTISODIY RIVOJLANISHINING ASOSIY YO‘NALISHLARI: MUAMMO VA YECHIMLAR - Qodirova , Dilnura; Sirojiddin , Saitov (Scientific practical conference, 2025)
This article explores the essence of modern humanitarian education, its significance in the development of society, and the current challenges faced by this field in the era of globalization and rapid technological progress. The study emphasizes that the growing influence of digitalization and information technologies has increased the importance of humanitarian sciences in shaping critical thinking, moral awareness, and cultural identity. However, several urgent problems persist, such as the predominance of traditional teaching methods, the insufficient connection between educational content and real-life practice, and the weak development of students’ creative and analytical skills. The paper discusses the need to modernize humanitarian education by integrating innovative pedagogical technologies, adopting a competence-based approach, harmonizing national and universal human values, and enhancing teachers’ professional competencies. The findings suggest that modern humanitarian education serves as a crucial factor in ensuring the spiritual, cultural, and intellectual development of society and in forming the human capital necessary for sustainable progress.